Gui bloopers 2.0 : - Johnson, Jeff (Elsevier, 2008)
GUI Bloopers 2.0 looks at user interface design bloopers from commercial software, Web sites, Web applications, and information appliances, explaining how intelligent, well-intentioned professionals make these mistakes--and how you can avoid them. While equipping you with the minimum of theory, GUI expert Jeff Johnson presents the reality of interface design in an entertaining, anecdotal, and instructive way:Updated to reflect the bloopers that are common today, incorporating many comments and suggestions from first edition readers, Takes a learn-by-example approach that teaches how to avoid common errors...